Pengaruh Daya Tarik Wisata dan Word Of Mouth terhadap Keputusan Wisata Berkunjung ke Taman Hutan Kota di Kota Langsa - Erni Junaida (Universitas Samudra, 2019)
This research intends to know the influence of tourist attraction and word of mouth to tourists' visiting decision in city forest park kota langsa. Samples of this research are 96 respondents. Data analysis of this research is using multiple linear regression method and hypothesis testing is using t test, f test, and determination coefficient test (R2). The result of multiple linear regression is Y = 1,200 + 0,341 X1 + 0.137 X2. T test result shows that tourist attraction variable influenced significantly to tourist's visiting decision in city forest park kota langsa and word of mouth variable also influenced significantly to tourist's visiting decision in city forest park kota langsa. F test result shows that tourist attraction variable and word of mouth variable influenced significantly to tourist's visiting decision in city forest park kota langsa. Determination coefficient test shows that tourist attraction and word of mouth influenced tourist's visiting decision in city forest park kota langsa for 0,301 or 30,1 %.